Makers of Modern Strategy : From Machiavelli to the Nuclear Age - Edited by Paret, Peter (New Jersey Princeton University Press, 1986)
This text discusses Machiavelli, Maurice of Nassau, Gustavus Adolphus, Raimondo Montecuccoli, Vauban, Frederick the Great, Guibert, Bulow, Napoleon, Jomini, Clausewitz, Adam Smith, Alexander Hamilton, Friedrich List, Engels, Marx, Moltke, Schlieffen, Delbruck, Bugeaud, Gallieni, Lyautey, Alfred Thayer Mahan, Liddell Hart, De Gaulle, and other military strategists.
Include Index
Keywords: Military art and science -- Strategy -- Military history, Modern